THE CHALLENGES OF PROFESSIONAL COMPETENCE OF LVIV REGION MILITARY CONDUCTORS IN THE FIRST DECADES OF THE XXth CENTURY - Vadym HORBAL (Studia Universitatis Babeş-Bolyai. Musica, 2022)
Internal application and social functions of the orchestras of different military formations on the territory of Ukrainian lands during the first half of the XXth century had their own history, including Lviv Region. This Region as the whole Galicia had gone through the numerous political transformations and changes of political systems. Each of such transformation put forward new requirements to the military musical art, thus, to the activity of military conductors. The aim of the article is the analysis of the tasks, demands, social and cultural background of the conditions of work, potential audience, the peculiarities of performance repertoire, professional training of the membership of the orchestra companies and the conductors of the orchestra’s groups of the Regular Army during the first decades of the XXth century. Such investigation based on historical, structural and systemic methods has been made for the first time. The military subunits of Lviv region of the period of Austrian regime (infantry regiments 10, 15, 23, 30, 55, 80) involved in their units Germans, Czechs, Austrians, Hungarians and less numerously presented Russians and Poles (55 and 80 infantry regiments that had their headquarters in Lviv and dislocated partially in Stryj and Zolochiv). Each of them obligatory had their own musical groups: mainly brass or competent symphony orchestra which included numerous Czech musicians and trumpeters as a separate unit. Each orchestra performer, as a rule, played two different instruments (brass and stringed). Their work was supervised by bandmaster and warrant officer – tambour major (who supervised group’s training as a conductor of the orchestra and their preparation to the defile), they were mainly Austrians, Germans and Czechs. Besides applicable military functions the orchestras took part in the civilian ceremonies, divine services and funeral ceremonies, every week at holidays and Sundays they carried out unmounted and hoarse defile along the city with march and light music of European authors under arrangements of their conductors (namely, arrangements of folk songs and dances), performed programs of European classical music in concert halls; and in public places: in park platforms, skating rigs; they also made guest-performance tours to the recreation resorts. In 1918 with the formation of Polish State there were some transformations in musical sphere of Polish Army and the USS Army. The conductors of military orchestras of Lviv region of the first decades of the XXth century faced the vast complex of tasks: the ability to work with the variety of personnel in the open air (in the field), in the square, hoarse defile and unmounted defile) in the covered concert-theatrical, theatrical buildings; mastering, providing, creation and adaptation of the universal repertoires to the real performance, potential and concert conditions, ensuring the training conditions of the new generation to the range of professional orchestras of academic level, the creation of programs, which provide with image and representative functions of the army, as well as to satisfy the needs of social and cultural topicality.